(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In India, generally all market investment avenues are perceived to be risky by the investors. “A derivative is a synthetic construction designed to give the same profile of returns as some underlying investment or transaction, without requiring the principle cash outlay. They are called derivatives because they derive their value from the performance of the underlying instrument. Financial derivatives can be found in debt, equity, currency and commodity markets”. This study was undertaken to find out the awareness level of various capital market instruments and also to find out their risk preference in various segments. Options have peculiar quality under which the holder of the option has been given right to buy or sell an underlying asset at a specified period for a fixed premium, Options trading strategies used by speculators, hedgers and arbitrageurs and to find out the type of risk which are concerned by the investors. Options can be used to create portfolio with unique features, capable of achieving investment objectives. Keeping this view the present paper proceeds to investigate the dynamic operational strategies and performance of options trading in India.